2006
DOI: 10.1111/j.1747-0803.2006.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Lung Perfusion Distribution in Normal Lung Scans: Observations and Clinical Implications

Abstract: The long-standing 55/45 right/left perfusion ratio assumption was found to be more than 1 standard deviation greater than the mean, and the population variance is very small. Relative pulmonary perfusion distribution varies significantly with lung region, gender, and age, and should be considered when making clinical decisions based on pulmonary perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Our methodology accounted for the deposition in all lung regions truncated in the SPECT/CT FOV by calculating the lung count density (counts/g) from the available left lung SPECT/CT VOI at least 2 cm from the CT liver contour and then multiplying by the total lung mass (g) from the diagnostic chest CT lung VOIs. The implicit assumption that the biodistribution of 99m Tc‐MAA was symmetrical in the left and right lungs was verified in our patient population (Section 3.C.2 ) ; furthermore, this assumption was also found to be valid in healthy lungs . We found that using only the left lung VOI (excluding the 2‐cm liver expansion) successfully minimized liver shine‐through in the left lung in the few cases with high superior left lobe liver 99m Tc‐MAA deposition.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our methodology accounted for the deposition in all lung regions truncated in the SPECT/CT FOV by calculating the lung count density (counts/g) from the available left lung SPECT/CT VOI at least 2 cm from the CT liver contour and then multiplying by the total lung mass (g) from the diagnostic chest CT lung VOIs. The implicit assumption that the biodistribution of 99m Tc‐MAA was symmetrical in the left and right lungs was verified in our patient population (Section 3.C.2 ) ; furthermore, this assumption was also found to be valid in healthy lungs . We found that using only the left lung VOI (excluding the 2‐cm liver expansion) successfully minimized liver shine‐through in the left lung in the few cases with high superior left lobe liver 99m Tc‐MAA deposition.…”
Section: Discussionsupporting
confidence: 67%
“…The implicit assumption that the biodistribution of 99m Tc-MAA was symmetrical in the left and right lungs was verified in our patient population (Section 3.C.2); furthermore, this assumption was also found to be valid in healthy lungs. 19 We found that using only the left lung VOI (excluding the 2-cm liver expansion) successfully minimized liver shine-through in the left lung in the few cases with high superior left lobe liver 99m Tc-MAA deposition. Although we observed some apico-basal variation of intensity in the lungs, the mean lung count density was calculated using most of the left lung in the FOV, and therefore minimally affected by local variation in intensity.…”
Section: C Lung 99m Tc-maa Distribution Estimationmentioning
confidence: 73%
“…The standard deviations seen in Table are relatively high, but this could be accounted for by the inclusion of semi‐large vessels and the inherent heterogeneity of blood flow in the lung. The perfusion values for both methods exhibit the expected right lung/left lung imbalance .…”
Section: Discussionmentioning
confidence: 87%
“…In fact, assigning a constant pressure condition would lead to a flow split entirely governed by the segmented (simulated) geometry [44], which is likely a non-physiologic result. In this case, the resistance parameters for the left and right branches are tuned to provide a normal flow split, i.e., 55% of the flow to the right side [45], leading to R RPA = 0.011 g mm −4 s −1 and R LPA = 0.017 g mm −4 s −1 . The resistive boundary condition was compared to a three-element Windkessel outflow model, assuming distal resistance coefficients equal to the ones reported above, a proximal resistance equal to 1/10 of the distal resistance, and a compliance coefficient equal to 10 mm 4 s 2 g −1 , as suggested in [36].…”
Section: Boundary Conditionsmentioning
confidence: 99%